Biotransformation of xenobiotics by hairy roots. (August 2020) - Jha, Pamela; Sen, Rajdip; Jobby, Renitta; Sachar, Shilpee; Bhatkalkar, Shruti; Desai, Neetin
Abstract: The exponential industrial growth we see today rides on the back of large scale production of chemicals, explosives and pharmaceutical products. However, the effluents getting released from their manufacturing units are greatly compromising the sustainability of our environment. With greater awareness of the imperative for environmental clean-up, a promising approach that is attracting increasing research interests is biodegradation of xenobiotics. In this approach, biotransformation has proven to be one of the most effective tools. While many different model frameworks have been used to study different aspects of biotransformation, hairy roots (HRs) have been found to be exceptionally valuable. HR cultures are preferred over other in-vitro model systems due to their biochemical stability and hormone-autotrophy. In addition, the multi-enzyme biosynthetic potential of HRs which is similar to the parent plant and their relatively low-cost cultural requirements further characterize their suitability for biotransformation. The recent progress observed in scale-up of HR cultures and understanding of functional genomics has opened up new dimensions providing valuable insights for industrial application. This review article summarizes the potential of HR cultures in the biotransformation of xenobiotics, their limitations in the application on a large scale and current strategies to alleviate them. Advancement in bioreactors engineering enabling large scale cultivation and modern gene technologies improving biotransformation efficiency promises to extend laboratory results to industrial applications. Graphical abstract: Image 1 Highlights: Biotransformation reactions of major xenobiotics by hairy roots. Major limitations in large scale applications of HRs for biotransformation. Current strategies for commercial use of HRs for biotransformation of xenobiotics.